(untitled) (AYUSHDHARA, 2024)
Avascular necrosis is a clinical condition where there will be cellular death of the bone components as a result of interruption to the blood supply. According to Ayurveda this condition can be studied under Vatarakta and Asthimajjagata vata or Asthi kshaya depending on the chronicity. Materials and methods: This case series involves four cases diagnosed with Avascular necrosis of femur and treated with various treatment modalities like, Sarvanga parisheka, Basti and Shashtikashali pinda sweda depending on the clinical presentation and the severity of the disease. Result: There was significant reduction in the symptoms of Avascular necrosis in all the 4 cases and considerable changes in the MRI of one patient. Conclusion: According to Ayurveda there is no direct correlation for this disease. If the disease is treated based on the chronicity and the pathogenesis involved, significant result can be obtained.